Contested Cosmopolitanisms: Global Meetings and Local Mobilizations1. Issue 1 (March 2015) - Kutz‐Flamenbaum, Rachel V.; Duncan, Brittany
<x xml:space="preserve">Abstract</x> This article analyzes the ways that Pittsburgh anarchist activists, politicians, and journalists framed the 2009 G‐20 meetings and protests through a content analysis of newspaper articles and activist documents. Our analysis found that cosmopolitanism was a central discourse, but it was also contested. Pittsburgh anarchists introduced an open‐community cosmopolitanism that prioritizes the local over the global as a site of struggle and also embraces expansion of rights and commitment to diversity and inclusivity. Somewhat unexpectedly, this open‐community cosmopolitanism was successfully transmitted beyond activist discourse into the public and the local media. The anarchist activist open‐community framing challenged Pittsburgh residents to question whether increased global corporate investments were best for Pittsburgh and, in doing so, fostered connections between local anarchist activists, local journalists, and local Pittsburgh residents. To reflect on the ways that activists contribute to ideas of cosmopolitanism, this article presents a theoretical model that incorporates individual and collective dispositions and multiple ideological standpoints. We also show how movement groups may strategically draw on these shared cosmopolitan dispositions to expand their movement base, communicate their messages, and challenge the hegemony of global capitalism.